Beautiful TV The Art and Argument of Ally McBeal - Smith, Greg M. (University of Texas Press, 2021)
During its five-year run from 1997 to 2002, the popular TV show Ally McBeal engaged viewers in debates over what it means to be a woman or a man in the modern workplace; how romance factors into the therapeutic understanding of relationships; what value eccentricity has and how much oddity society should tolerate; and what utility fantasy has in the pragmatic world. In addition to these social concerns, however, Ally McBeal stood out for being well-constructed, narratively complex, and stylistically rich-in short, beautiful TV. Starting from the premise that much of television today is "drop-dead gorgeous" and that TV should be studied for its formal qualities as well as its social impact, Greg M. Smith analyzes Ally McBeal in terms of its aesthetic principles and narrative construction. He explores how Ally's innovative use of music, special effects, fantasy sequences, voiceovers, and flashbacks structures a distinctive fictional universe, while it also opens up new possibilities for televisual expression. Smith also discusses the complex narrative strategies that Ally's creator David E. Kelley used to develop a long-running storyline and shows how these serial narrative practices can help us understand a wide range of prime-time TV serials. By taking seriously the art and argument of Ally McBeal, Beautiful TV conclusively demonstrates that aesthetic and narrative analysis is an indispensable key for unlocking the richness of contemporary television